2008
DOI: 10.1002/iroh.200710976
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fish Assemblage Diversity in Natural and Artificial Rip‐Rap Habitats in the Littoral Zone of a Large River (River Danube, Hungary)

Abstract: We studied day-night patterns in fish diversity in natural, gravel-sand stretches and boulder covered rip-rap habitats in the littoral zone of the River Danube. Sample-based rarefaction indicated marked differences in species richness between day and night, and smaller differences between habitats for both day and night. Whereas, individual-based rarefaction indicated no such substantial differences in species richness. However, distinct fish assemblages were found based on relative abundance data, and species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 52 publications
3
53
1
Order By: Relevance
“…The maximum size achieved by round goby from the invasive population in the Karlova Ves side-arm (153 mm SL, 183 mm TL in males; 134 mm SL, 164 mm TL in females) represents the biggest size ever recorded from the Slovak stretch of the Danube, and it appears to be similar to that reported for other invasive Danubian populations: 150 mm SL in Austria [28] 160 mm SL in Hungary [29]. In North America, the biggest male of round goby from the invasive population in the River Detroit achieved 124 mm TL; female 112 mm TL, and the lengths in individual age groups were also similar to those from the Karlova Ves side-arm [30].…”
Section: Discussionsupporting
confidence: 71%
“…The maximum size achieved by round goby from the invasive population in the Karlova Ves side-arm (153 mm SL, 183 mm TL in males; 134 mm SL, 164 mm TL in females) represents the biggest size ever recorded from the Slovak stretch of the Danube, and it appears to be similar to that reported for other invasive Danubian populations: 150 mm SL in Austria [28] 160 mm SL in Hungary [29]. In North America, the biggest male of round goby from the invasive population in the River Detroit achieved 124 mm TL; female 112 mm TL, and the lengths in individual age groups were also similar to those from the Karlova Ves side-arm [30].…”
Section: Discussionsupporting
confidence: 71%
“…Such behavior was particularly described for subadult and adult fish in rivers (Kubečka & Duncan, 1998;Wolter & Freyhof, 2004;Erös et al, 2008), some lakes (Schulz & Berg, 1987;Zamora & Moreno-Amich, 2002;Jacobsen et al, 2004) and reservoirs (Kubečka, 1993;Vehanen et al, 2005;Ř íha et al, 2011). The reason for such migration is poorly understood and several different explanations have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such sampling could also reveal the occurrence of potential predators and evaluate their impact on the diel distribution dynamics of different species and size categories. In European freshwaters, studies dealing with diel changes of fish distribution largely focused on only one species (Schulz & Berg, 1987;Zamora & Moreno-Amich, 2002;Jacobsen et al, 2004) or sampling of a community in only one zone (Brosse et al, 2007;Erös et al, 2008). However, there is a very limited number of studies that performed simultaneous quantitative sampling of the whole fish communities in both zones and periods (Wolter & Freyhof, 2004;Muška et al, 2013) and in our best knowledge there is no study providing picture of diel changes among all mentioned habitats simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…feeding, refuging). In fact white bream has been shown to move to the littoral zone of rivers by night (Wolter & Freyhof 2004, ErŐs et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…In freshwater systems for example, diel changes have been found to be significant in the littoral zone of lakes and reservoirs (Baumann & Kitchell 1974, Lewin et al 2004, Riha et al 2015 and rivers (Sanders 1992, Copp & Jurajda 1993, Arrington & Winemiller 2003, ErŐs et al 2008. Several studies showed that night time samplings yielded more species and specimens and greater biomass than day time samplings in the nearshore habitats of rivers because of higher catching efficiency, diel migration of many species to the littoral zone and higher movement activity by night (Copp & Jurajda 1993, Wolter & Freyhof 2004, ErŐs et al 2008. It was concluded that both diurnal and nocturnal samplings are required to adequately characterize fish assemblages, especially in large rivers, which are difficult to sample representatively (Wolter & Freyhof 2004, Copp et al 2005, Baumgartner et al 2008.…”
Section: Introductionmentioning
confidence: 99%